Application of laparoscopic artificial insemination in conventional Lacaune sheep farm using frozen-thawed semen - Zegeye, Zemenu Birhan; Vass, Nóra; Tomano, Andualem (Acta Agraria Debreceniensis, 2020)
The complex anatomical structure of the ewe reproductive tract accompanied with low quality of frozen ram semen for artificial insemination, resulted in a challenge with regard to using superior genotypes for reproductive ovine performance. Hence, improved genetics in ovine management has not been efficiently and widely used especially in undeveloped countries. Therefore, intrauterine semen deposition by laparoscopic insemination should be adopted in the current sheep production systems. Thus, this study aimed to assess the pregnancy rate and lambing rate of ewe inseminated by laparoscopic insemination techniques using frozen-thawed semen. The research used imported frozen semen from two rams of the Lacaune breed. Ewes were grouped according to age in years (1, 2 and 4). Before insemination, the semen was examined microscopically for its motility and viability and thereafter the laparoscopic artificial insemination technique was performed to 19 Lacaune breed ewes using frozen-thawed semen. The overall pregnancy and prolificacy rates were 31.57% and 42.10% respectively. Out of 2 ewes in the 1-year age group that were inseminated, only 1 ewe lambed representing 50%. However, from 16 ewes inseminated of four-year age group, 5 ewes lambed representing 31.25%. Significant difference based on age group was not evaluated due disproportionate of the data, (such that the data included 2 ewes in one-year-old age, 1 ewe in 2-year-old age and 16 ewes in 4-year-old age). Based on the ram semen, 33.33% and 30% of the inseminated ewes were pregnant from ram A and ram B semen respectively. However, in the case of prolificacy rate, 44.44% and 40 % of the ewes lambed from using semen of ram A and B, respectively. There was no significant difference (p>0.05) in pregnancy and prolificacy rates based on semen from the two rams. In conclusion, in this research study, ram semen had no significant effect on pregnancy and prolificacy rates using laparoscopic AI on Lacaune sheep. This could be due to the fact that the rams had very good quality semen. Evaluation of ram semen, accompanied with appropriate ewe selection based on age and rightful deposition of semen could lead to better and more consistent results. Overall this could contribute to the successful application of laparoscopic artificial insemination in Lacaune sheep production systems for enhanced productivity.